Why marine gammarids belong to the future portfolio of aquafeed ingredients - Calado, Ricardo; Carvalho, Marta; Marques, Luísa; Rodrigues, Daniela P.; Sousa, João P.; Rey, Felisa; Domingues, Maria Rosário; Fernandes, Joana Filipa; Silva, Ruben X. G.; Madeira, Diana; Malzahn, Arne M.; Monroig, Óscar; et al. (Frontiers in Marine Science, 2025)
The sustainable supply of n-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA) remains a major challenge for global aquaculture. Although plant oils, microalgae, genetically modified crops, insects, krill, and fish by-products have been explored as alternative sources, none currently provides a stand-alone solution for meeting the growing demand of n-3 LC-PUFA in aquafeeds’ production. Here, we present marine gammarids as a potential complementary source of these fatty acids. Our Perspective article focuses on the nutritional attributes of marine gammarids, including their naturally high levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and considers their biological traits that support aquaculture practicality. We also examine the potential of marine gammarids for circular bioeconomy applications through trophic upgrading of low-value side streams. While evidence from feeding trials is limited, preliminary data suggest marine gammarids may maintain their high EPA and DHA content even when fed on low-quality diets. Critical research priorities include developing scalable production systems, optimising feed formulations, evaluating performance across key aquaculture species, and assessing ecological and operational feasibility. This Perspective also highlights the potential of marine gammarids to contribute to a diversified and resilient aquafeed portfolio. Although they are unlikely to replace fish meal or fish oil entirely, marine gammarids may serve as a strategic complementary ingredient.